Vaping Is Not Safe: A Case of Acute Eosinophilic Pneumonia following Cannabis Vapor Inhalation - Daniel Antwi-Amoabeng; Raheel Islam (Case Reports in Pulmonology)
There is a well-established association between inhalational exposures and acute eosinophilic pneumonia (AEP). The most reported exposure is cigarette smoking. Here, we present a case of progressive shortness of breath and nonproductive cough in a college student with no significant medical history, approximately 10 days after inhaling cannabis aerosols on two separate occasions. He was started on empiric antibiotics and bronchodilators without improvement. He was diagnosed with AEP based on peripheral eosinophilia and high-resolution CT image results. He made rapid recovery on intravenous glucocorticoids. Vaping has gained popularity among young adults mainly due to the perception that it is a safe alternative to smoking. This case shows that there may be a false sense of security with vaping. Vaping poses a yet-to-be quantified public health threat, which requires further studies.